The effect of virtual reality on pain, anxiety, and physiological parameters in patients undergoing gastroscopy - Turan, Gulcan Bahcecioglu; Ozdemir, Hatice (Sage Publications Ltd, 2026)
Background: Patients undergoing gastroscopy may experience discomfort and heightened anxiety because they remain conscious throughout the procedure and may fear possible complications. Objective: This study examined whether a virtual reality (VR)-based relaxation intervention influences pain intensity, anxiety levels, and physiological anxiety indicators in patients undergoing gastroscopy. Methods: A randomized controlled, parallel-group design was used. The sample consisted of 78 patients, with 39 allocated to the VR intervention group and 39 to the control group. Patients in the intervention group viewed a five-minute relaxation program via VR goggles before and during the procedure, while the control group received standard care. Data were collected using the Patient Information Form, Visual Analog Scale-Pain (VAS-P), Visual Analog Scale-Anxiety (VAS-A), and Physiological Parameters of Anxiety Monitoring Form. Results: Compared with the control group, patients receiving VR showed significantly lower post-intervention VAS-P and VAS-A scores, heart rate, systolic and diastolic blood pressure, and respiratory rate. Oxygen saturation levels were significantly higher (p < 0.05). Conclusion: The VR relaxation intervention was associated with lower levels of pain, anxiety, and physiological stress responses, as well as higher oxygen saturation during gastroscopy. These findings suggest that VR applications may be considered as a supportive adjunct in gastroscopy nursing care to enhance patient comfort and safety.
Keywords: Gastroscopy; upper gastrointestinal endoscopy; virtual reality; pain; anxiety; physiological parameters